2016
DOI: 10.1016/j.egja.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus fentanyl in anesthesia of cochlear implantation in pediatric patients

Abstract: Background: Anesthesia for cochlear implantation in pediatrics mandates deliberate hypotension to provide a better surgical field. Dexmedetomidine is a 2 adrenoceptor agonist that provides adequate sedation with high cardiovascular stability. We aimed to compare it with fentanyl as an anesthetic adjuvant. Methods: 52 pediatric patients (ASA I or II), undergoing cochlear implantation were randomized into dexmedetomidine (D) group and fentanyl (F) group (n = 26 for each). Anesthesia was induced by I.V. dexmedeto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…It allowed rapid recovery from anesthesia and reduced need for pain medication in the PACU. [ 15 ] These findings correlate with the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It allowed rapid recovery from anesthesia and reduced need for pain medication in the PACU. [ 15 ] These findings correlate with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the intraoperative reduction in hemodynamic parameters (MAP and HR) in both groups was within 20% from baseline values. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our result, El Saied et al reported that dexmedetomidine infusion in pediatric patients allowed rapid recovery from anesthesia and reduced need for analgesic requirements in the postoperative period [36].…”
Section: Discussionsupporting
confidence: 80%
“…El Saied MH found that, Dexmedetomidine infusion in cochlear implantation in pediatric patients was better in inducing deliberate hypotension and providing better quality scale of surgical field compared to fentanyl infusion. It allowed rapid recovery from anesthesia and reduced need for pain medication in the PACU [28].…”
Section: Discussionmentioning
confidence: 99%